Systemic changes after 4 months of swimming training - Monteiro, C. P.; Morgado, J.; Matias, C.; Alves, F.; Seixas, M. T.; Alvim, M.; Bourbon, M.; Laires, M. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: In endurance sports such as Swimming the implementation of cycles of high training volume in order to optimize aerobic and movement economy adaptations can lead to transient imbalances between training loads and recovery contributing to the onset of fatigue and eventually illness in well trained athletes. An immunodepression state characterized by substrate depletion, hormonal and immune functions disturbances is usually the response to hard training periods. The purpose of this study was to evaluate the effects of a 4-month swim training macrocycle of preparation for the Winter Swimming National Championships over the resting systemic immunity. Methods: Systemic immunity was assessed in 35 Portuguese male swimmers (15.8 ± 0.32 yrs; 187 ± 14.6 cm; 63.8 ± 1.4 kg) at the beginning of the training season (M1) and at the end of the winter National Championships (M2). This macrocycle was characterized by an aerobic training predominance and the progressive increase of training volumes and intensities in the first 3 months and for the maintenance of high intensities and progressive decrease of volumes in the last month. At the National Championships swimmers have accomplished at least one personal best time in the races they were enrolled in. Blood samples were collected by standard procedures for assessment of haemogram and leukogram (automated counter Beckman Coulter LH 750) and lymphocytes subpopulations (FACS Calibur Becton, Dickinson and Company) including CD3+, CD4+, CD8+, CD16+ and CD19+. Paired samples t test or Wilcoxon test was used to compare M1 and M2 resting values of each variable. The level of significance was set at p<0.05. Results: At M2 we observed significant higher resting levels of haemoglobin, haematocrit, red blood cells, and neutrophils. Contrarily, total lymphocytes (%) were significantly diminished. Discussion During this training cycle it was observed a stimulation of innate immunity (represented essentially by neutrophils) and a decline in the adaptive immunity (represented by total lymphocytes) that may be associated with the higher performance levels observed after a swimming winter macrocycle. These alterations may reflect the cumulative effects of aerobic training predominance suggesting that training load volume may be determinant for systemic change.